If blockchain is the solution, robot security is the problem - Ferrer, Eduardo Castelló (Frontiers in Blockchain, 2023)
Robotics systems of all types are revolutionizing a wide variety of industries---transportation, manufacturing, and even healthcare---and yet, many essential ingredients for robotics systems in the real world are not technologically ready for deployment. Currently, robots lack the protocols and standards required to be safe and secure outside factories. In an attempt to close this gap, recent research has demonstrated the security benefits of combining robotics systems with blockchain-based technology (e.g., smart contracts, zero-knowledge proofs, Merkle trees). In this perspective article, I argue that blockchain-based robotics is starting to provide innovative solutions (e.g., secure data sharing, consensus mechanisms, and new interaction methods) to urgent problems of robot security. I list the most important takeaways so far from this emerging field of research that I helped establish together with a growing community. I close the article by discussing the impending implications of the security challenges that the robotics research community is facing, and possible ways for us to move forward.